Indonesia and Saudi Arabia Partnership During Regional Pressure on Hajj Management - Faikha Fairuz Firdausi; Laras Putri Olifiani; Moh. Talabul Amal; Intan Iswandi (Islam Realitas: Journal of Islamic and Social Studies, 2023)
This paper discusses the relationship between Indonesia and Saudi Arabia in managing the pilgrimage. Hajj is a sector that makes a significant contribution to the economy of Saudi Arabia. However, the increasing number of pilgrims every year makes managing the pilgrimage more difficult and makes Saudi Arabia face regional pressure in the form of internationalizing the management of the pilgrimage. During regional pressure, Saudi Arabia is trying to diversify its economy through Saudi Vision 2030 which contains plans to improve the governance of the Hajj and Umrah pilgrimages. Indonesia, one of the countries that cares about pilgrims, is often faced with facts related to the inefficient management and services of Hajj. Through the concept of national interest, this research shows that the internationalization pressure of hajj has become a stimulus for Saudi Arabia in improving the management of its hajj in line with its 2030 vision which also focuses on hajj issues. The collaboration of these two factors has made Indonesia, a close partner of Saudi Arabia in hajj activities, will have a positive effect in the form of increased aspects of service and mobility that will make it easier for Indonesian pilgrims to perform the pilgrimage.